Global Longitudinal Strain (GLS) in Elderly and Its Associated Factors - Mohamad Syahrir Azizi; Sally Aman Nasution; Siti Setiati; Hamzah Shatri (Acta Medica Indonesiana)
Background: cardiovascular disease is very common and can be fatal in elderly patients. It is often preceded by asymptomatic or subclinical left ventricular systolic dysfunction (LVSD). Early detection of LVSD can reduce morbidity and mortality due to cardiovascular disease. One method used in the early detection of LVSD is an assessment of global longitudinal strain (GLS). This study aimed to determine the mean value of GLS and GLS-related factors. Methods: this cross-sectional study was conducted among elderly patients aged > 60 years in the geriatric and cardiology clinic, Internal Medicine, CMH Hospital. Data were obtained from interviews, medical records, and transthoracic echocardiography examination. The variables of age, frailty, hypertension, coronary artery disease, dyslipidemia, and diabetes mellitus were analyzed as the determinants of a decrease in GLS. Univariate analysis was conducted for each variable. Bivariate analysis was conducted using the chi-square test with a significance level of p<0.25 and confidence interval (CI) of 95%, and multivariate analysis used a logistic regression test. Results: a total of 194 patients were admitted according to the study criteria, with a mean age of 66 years. The proportion of women was 60.8%. The study revealed that the determinants with p<0.25 are frailty, hypertension, dyslipidemia, and diabetes mellitus, with multivariate analysis frailty having an OR of 2.002 (95% CI 1.042–3.925) and diabetes mellitus having an OR of 2.278 (95% CI 1.033–5.025). Conclusion: the mean value of GLS among the elderly was -21.6% (minimum value -5.3% and maximum value 29.9%). The factors that influence the decrease of GLS are frailty and diabetes mellitus.